Optical clearing of the eye using the See Deep Brain technique - Hohberger, B.; Baumgart, Carina; Bergua, A. (Eye, 2017)
PurposeTissue clearing has been used in anatomy for the first time in Germany over a century ago. Neuronal tissue, like cortex, was investigated in mice using a water-based optical clearing method termed See Deep Brain (SeeDB). However, although the eye belongs to the central nervous system, this histological technique was not applied in the eye up to date. We applied SeeDB for the visualization of intraocular structures.Patients and methodsFour eyes of cornea donors (two male, two female: 73-84 years) obtained from the Cornea Bank of the Department of Ophthalmology Erlangen, four chicken eyes and two mices' optic nerve were used. Bulbi were fixed in 4% paraformaldehyde in phosphate-buffered saline and treated with increasing concentrations of aqueous fructose solution with 0.5% ?-thioglycerol. After SeeDB, transscleral macrophotographs of the choroid were performed.ResultsComplete transparency of the sclera was obtained in enucleated human and chicken eyes after SeeDB treatment. Macroscopical anatomy of the choroid (partially transparent due to the remaining retinal pigment epithelium and melanocytes) showing vessels and other related structures was possible without preparing slides. Mice optic nerves were also transparent after SeeDB treatment.ConclusionThe SeeDB method allows visualization of intraocular structures through a completely translucent sclera. This innovative processing technique could facilitate comprehensive qualitative and quantitative topographical anatomical studies of human and animal eyes, preserving their 3D architecture. Supra- and intrachoroidal ganglionic plexus could potentially be visualized transsclerally. Finally, clinical-pathological correlations of intraocular diseases-for example, retinal tumors-will be possible in non-dissected eyes.Eye advance online publication, 2 June 2017; doi:10.1038/eye.2017.83.
EVALuna2:21275